Faktor Internal dan Eksternal yang Mempengaruhi Pembiayaan Bank Pembiayaan Rakyat Syariah (Periode 2011 – 2019) - Anggraini, Aprilia; Nugroho, Ris Yuwono Yudo (Jurnal Iqtisaduna, 2021)
This research aims to (1) determine the long-term and short-term relation of internal factors for financing the Sharia People's Financing Bank in Indonesia, (2) determine the long-term and short-term external relation factors for financing the Sharia People's Financing Bank in Indonesia. This research uses a descriptive quantitative method. This study uses time-series data in a monthly form for 2011: M01 to 2019: M12. The analysis technique uses the Autoregressive Distributed Lag model. The research result shows the following: (1) Capital Adequacy Ratio has a negative and significant effect on Indonesia's BPRS financing in the long-term and short-term. (2) Long-term Third Party Funds has a positive and significant impact on BPRS financing. In the short term, Third Party Funds have a positive and significant impact on BPRS financing at lag 2. (3) Inflation has a positive and insignificant impact on the long-term and short-term BPRS financing in Indonesia. (4) Industrial Productive Index has a positive and significant impact on Indonesia's BPRS financing in the long-term and short-term.